2014
DOI: 10.3233/jad-141002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin Profile Changes are Associated to the Early Synaptic Mitochondrial Dysfunction in Alzheimer's Disease

Abstract: Brain mitochondria are fundamental to maintaining healthy functional brains, and their dysfunction is involved in age-related neurodegenerative disorders such as Alzheimer's disease (AD). In this study, we conducted a research on how both non-synaptic and synaptic mitochondrial functions are compromised at an early stage of AD-like pathologies and their correlation with putative changes on membranes lipid profile, using 3 month-old nontransgenic and 3xTg-AD mice, a murine model of experimental AD. Bioenergetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 59 publications
7
99
1
1
Order By: Relevance
“…Increasing evidence has implicated altered brain CL in the pathologic development of cognitive dysfunction in aging and multiple neurodegenerative disorders including Alzheimer’s disease and Parkinson’s disease 20,27,45,46 . However, a link between CL and cognitive impairment has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has implicated altered brain CL in the pathologic development of cognitive dysfunction in aging and multiple neurodegenerative disorders including Alzheimer’s disease and Parkinson’s disease 20,27,45,46 . However, a link between CL and cognitive impairment has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that alterations of CL profile in brain of AD animal model are associated with synaptic mitochondrial dysfunction and oxidative stress 51 . In brain of HFD fed mice we identified 5 elevated CL molecular sub-species (68:4; 70;4; 72:4; 74:7; 84:20) and 2 (72:6; 76:11) with decreased amounts (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, cardiolipin in nonsynaptic mitochondria appears to be less resistant to aging‐mediated changes, undergoing a decrease in total content with advancing age, while the cardiolipin content of synaptic mitochondria remains well preserved . Conversely, in at least one model of Alzheimer's Disease, synaptic mitochondria are shown to undergo a decline in most cardiolipin species, while it is the non‐synaptic mitochondria that are well maintained .…”
Section: Tissue‐specific Molecular Cardiolipin Compositionmentioning
confidence: 99%
“…Alterations in the cardiolipin content or composition of brain may have pathological consequences . Decreases in the total cardiolipin content of brain mitochondria have been reported in Parkinson's Disease , Alzheimer's Disease , and in age‐related dementia . Changes in the fatty acyl composition of brain cardiolipin are also reported.…”
Section: Tissue‐specific Molecular Cardiolipin Compositionmentioning
confidence: 99%